Tectonic Controls on Global Variations of Large-Magnitude Explosive Eruptions in Volcanic Arcs - Sheldrake, Tom; Caricchi, Luca; Scutari, Marco (Frontiers in Earth Science, 2020)
Linking tectonic setting to eruptive activity in volcanic arcs provides a framework to understand processes that control the production, accumulation and eruption of magma on Earth. We use the Holocene eruptive records of 162 volcanoes, which are selected based on an assessment of recording biases, to calculate the probability of recording eruptions of different magnitude. We examine how variability in the sizes of volcanic eruptions up to Magnitude 7 varies with subduction parameters. Given the tectonic setting of a subduction zone is multidimensional (e.g., age, speed, obliquity of the subducting plate) we use a graphical model to explore the strength of probabilistic relationships between tectonic and volcanic variables. The variable that exhibits the strongest probabilistic relationship with eruption size is subduction obliquity, with larger eruptions favoured in settings where subduction is normal. We suggest this favours the storage of magma, meaning that with sufficient magma productivity, accumulation and eruption of larger volumes of magma occurs. Based on the age of the subducting slab and subduction obliquity, we distinguish two broad behavioural regimes. The first regime is characterised by older subducting slabs and low subduction obliquity, in which the accumulation of eruptible magma in the shallow crust is dominantly controlled by magma productivity. In volcanic arcs whose behaviour is dominated by this regime, larger eruptions occur in arcs with younger subducting slabs (i.e. intermediate magma productivity). We suggest this is because the highest magma productivity (i.e. older slab ages) will likely lead to frequent replenishment of subvolcanic magma reservoirs, resulting in overpressurisation and eruption. The second regime is characterised by younger subducting slabs and higher subduction obliquity, in which we suggest extension (e.g. pull-apart basins) favours vertical magma transport through the crust. This leads to frequent injection of magma into the upper crust, favouring eruption rather than long-term storage. Consequently, eruptions in these volcanic arcs are on average smaller than eruptions in arcs whose behaviour is dominated by the first regime. In arcs whose behaviour is dominantly controlled by the second regime larger eruptions occur where the crust is thicker, which we suggest favours magma accumulation with respect to thinner crust.